Identification of Possible Stellar Companions via Speckle Interferometry in a Sample of Be Stars II - C. A. Guerrero; T. B. Souza; M. Borges Fernandes; A. D. Guajardo Jurado (The Astronomical Journal)
This study investigates the identification of possible stellar companions in a sample of Be stars using speckle interferometry. Be stars, which are rapidly rotating B-type stars exhibiting emission lines due to the presence of circumstellar disks, have been proposed to potentially reside in binary or multiple systems, which could influence their mass transfer processes and disk dynamics. We conducted observations of 46 Be stars using the 2.1 m telescope at the Observatorio Astronómico Nacional, Sierra San Pedro Mártir, Mexico, over two observing campaigns in 2018. With our observations, we identified secondary companions in 12 of the observed stars, five of which are new interferometric pairs. The angular separations of these newly identified pairs ranged from 0 $\mathop{.}\limits^{^{′′} }$ 09 to 0 $\mathop{.}\limits^{^{′′} }$ 33, with a maximum magnitude difference of Δ m = 4.72 noted for star HD 41335. We estimated an observed multiplicity rate of ∼26% for our sample, thus reinforcing the existing knowledge of the multiplicity of Be stars. To further investigate the gravitational binding potential of the identified systems, we cross referenced our findings with data from Gaia Data Release 3. This analysis revealed that many potential companions, although not detected in our observations, were too faint (with G magnitudes ≥ 15.2) or too distant (separations greater than 2 $\mathop{.}\limits^{^{′′} }$ 0) to exert a significant influence on the circumstellar disk dynamics of the primary Be stars.